Effects of hyaluronic acid on bleeding following third molar extraction - YARAT, AYŞEN; GÖKER, BAHAR; GÖÇMEN, GÖKHAN (UNIV SAO PAULO FAC ODONTOLOGIA BAURU, 2017)
Objective: To explore the effects of hyaluronic acid (HA) on bleeding and associated outcomes after third molar extraction. Methods: Forty patients who had undergone molar extraction were randomly divided into two groups; 0.8% (w/v) HA was applied to the HA group (n = 20) whereas a control group (n = 20) was not treated. Salivary and gingival tissue factor (TF) levels, bleeding time, maximum interincisal opening (MIO), pain scored on a visual analog scale (VAS), and the swelling extent were compared between the two groups. Results: HA did not significantly affect gingival TF levels. Salivary TF levels increased significantly 1 week after HA application but not in the control group. Neither the VAS pain level nor MIO differed significantly between the two groups. The swelling extent on day 3 and the bleeding time were greater in the HA group than in the control group. Conclusions: Local injection of HA at 0.8% prolonged the bleeding time, and increased hemorrhage and swelling in the early postoperative period after third molar extractions.
Keywords: Hyaluronic acid; Bleeding; Extraction; TISSUE FACTOR